Quintessential cities, accountable to the future : sustainability, innovation and citizenship - Mega, Voula (Springer New York, 2013)
This book can be seen as the third part of an unofficial trilogy on Sustainable Cities of the Future with the author's previous books 'Sustainable Development, Energy and the City' and 'Sustainable Cities for the third millennium: The Odyssey of urban excellence', both prefaced by Prof. Sir Peter Hall. All three books follow the evolving forefront of innovations towards Sustainable Cities. They collectively try to respond to the questions: What future cities wish to build (with their scarcities and capacities) on a finite planet? What do-they do to achieve this? How do-they contribute to redesign the world?  The third book adopts, first and foremost, a strategic foresight approach including a scan of the future trends, tensions and risks in a more uncertain world, the possible and preferable futures, emerging policy issues, such as intergenerational  cities or cities welcoming the immigrants and their impact on sustainable development, the Rio+20 prospects and the effects of the protracted crisis, efforts by world interconnected cities, including a case-study on Bangkok, a laboratory of urban change, and examples of frugal and resilient urban policies.